Mating suppression of the Mediterranean flour moth (Ephestia kiihniella Zeller) (Lepidoptera Pyralidae) in a food industry (Bollettino di zoologia agraria e bachicoltura, 2024)
Infestation of Ephestia kiihniella in a food industry was controlledby using laminar and "rubber string" dispensers imbued with a high quantity ofTDA. Trials lasted more than two years. The dispensers were placed on the wallsand under the machineries in crevices with high infestation. The matingsuppression can be obtained when a daily average distribution of 2.5 (±1) μg/m3of TDA for at least 4 months has been mantained.
Keywords: Ephestia kiihniella; mating suppression; TDA; Mediterranean flour moth